(untitled) (JURNAL ADMINISTRASI PUBLIK, 2019)
To realize regional capability and independence and strengthen the structure of regional revenues, the contribution of locally generated revenue in the state expenditure bedget structure must always be improved because it is one of the benchmarks of capability and a mirror of regional independence. Market retribution is an important source of regional income in addition to resources. other income that has a strategic role in the framework of financing regional development so that the increase in research market retribution uses an interactive analysis model and SWOT analysis. Therefore, the research is the Strategy for Increasing Youtefa’s Market Retribution as One of the Sources of Local Revenue in the City of Jayapura. This study uses Qualitative Research Methods using SWOT analysis techniques. Analysis of internal factors produces factors of strength and weakness. Strengths (Strenghts), namely the Authority / Authority granted by the City Government, Training for improvement of Human Resources (HR), Retribution collection procedures, Making facilities for traders, Clarity of mandate of youtefa market organizations. Weakness factors are low formal education, low financial ability to meet the budget, low compassion competency, lack of functional education, weak supervision and law enforcement functions. External factors produce opportunities and threats. Opportunities are the legal foundation for managing market retribution, good economic growth, increasing community income, community education. Threat Factors (Thrreats), namely the involvement of many parties in determining retribution rates, Weak law enforcement, Inadequate infrastructure and facilities, low levels when the government pays the market. Based on a SWOT analysis, ten strategies. Keywords: Strategy, Market Retribution, Regional Original Income.